2017
DOI: 10.7189/jogh.07.010404
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol–attributed disease burden and alcohol policies in the BRICS–countries during the years 1990–2013

Abstract: BackgroundWe aimed to assess alcohol consumption and alcohol–attributed disease burden by DALYs (disability adjusted life years) in the BRICS countries (Brazil, Russia, India, China and South Africa) between 1990 and 2013, and explore to what extent these countries have implemented evidence–based alcohol policies during the same time period.MethodsA comparative risk assessment approach and literature review, within a setting of the BRICS countries. Participants were the total populations (males and females com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
(62 reference statements)
0
15
0
Order By: Relevance
“…In China, the alcohol taxes were increased in 2002, and the alcohol sale restrictions and the license requirement were implemented in 2004. In 2007, the laws that punish drunk drivers began to be enforced, and restrictions on alcohol advertisements took effect in 2010[87]. However, the alcohol policy in China is weaker than those in its neighboring countries in many aspects, which favors alcohol consumption, leading to consequent alcohol-related problems.…”
Section: Management Of Ald In Chinamentioning
confidence: 99%
“…In China, the alcohol taxes were increased in 2002, and the alcohol sale restrictions and the license requirement were implemented in 2004. In 2007, the laws that punish drunk drivers began to be enforced, and restrictions on alcohol advertisements took effect in 2010[87]. However, the alcohol policy in China is weaker than those in its neighboring countries in many aspects, which favors alcohol consumption, leading to consequent alcohol-related problems.…”
Section: Management Of Ald In Chinamentioning
confidence: 99%
“…Alcohol consumption accounts for approximately 4% of all-cause global mortality and 5% of the global disease burden ( Beaglehole & Bonita, 2009 ). As such, alcohol is recognised by healthcare systems as a major risk factor for a host of physical and psychological illnesses, injuries, and self-harm, as well as social issues that create significant bearing on indicators such as potential years of life lost, and disability-adjusted life years ( Lam & Chim, 2010 ; Collin, Hill & Smith, 2015 ; Rabiee et al, 2017 ; Shield et al, 2012 ). Advances in molecular pathology has greatly facilitated the understanding of the underlying mechanisms through which alcohol affects major regulatory systems leading to endocrine disorder and associated consequences such as disruption of the circadian rhythm (Process C) ( Emanuele & Emanuele, 1997 ; De Coster & Van Larebeke, 2012 ; Rachdaoui & Sarkar, 2013 , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The burden tends to be highest in Russia, however, with significant reduction starting from 2005 and at a similar and relatively stable level in the remaining countries. South Africa appeared to be an exception here, with a higher burden than in China, India, and Brazil and an observable rising trend up to 2000, and later decrease, which appeared to be against the trend in alcohol consumption (32).…”
Section: Discussionmentioning
confidence: 70%
“…The authors of the study also identified mortalities in BRICS countries as being more strongly connected to deficiencies in prevention, early detection, and treatment, when compared to developed countries (31). Rabiee et al (32), in turn, analyzed the correlation between alcohol consumption and disease burden in BRICS countries. Trends and observation in this case are to some extent different from those arising of our study.…”
Section: Discussionmentioning
confidence: 99%